Hot water treatments performed in the base of the floral stem reduce postharvest senescence of cutting lily = Os tratamentos com água quente realizados na base do caule floral reduzem a senescência pós-colheita do lírio de corte - Mantilla Alarcon, Alfredo Gunther; Mascarini, Libertad; Chludil, Hugo Daniel; Martínez, Gustavo Adolfo (Sociedade Brasileira de Floricultura e Plantas Ornamentais (SBFPO), 2025)
Lilies are commonly grown and marketed as cut flowers. Harvesting causes considerable stress, which triggers accelerated senescence, making this process a limiting factor of their postharvest life. Senescence control is achieved through various methodologies, including moderatetemperature thermal treatments for a short time. These treatments cause mild stress that can affect the tissues metabolism. This study aimed to determine the quality, postharvest life, and metabolism of Lilium longiflorum after applying thermal stress to the base of the flower stems. Heat treatments were performed by using hot water (50 °C during 5 min) in the first 2 cm above the cut on the stalk, while a similar treatment was carried out with water at 20 °C for the controls. The treated stems showed less weight loss and water consumption; but the buds opened later. Similarly, less senescence and chlorophyll loss were observed in the leaves of the treated samples. A trend towards a higher concentration of phenols was observed in the first days of storage in the leaves and tepals of the treated stems, no significant variations in flavonoid content were detected. Lower amounts of TBARS and less electrolyte loss were detected in the heat-treated samples, indicating less peroxidation and greater membrane stability. The treatment also induced higher anthocyanin accumulation in tepals. The results suggest that the hot water thermal treatment in postharvest is an appropriate method to improve stem freshness, bud opening degree, and delay senescence, prolonging vase life without negative effects during storage.